USE OF METAPHORS IN THE STORY OF THE HORSE NIGHT (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article analyzes the metaphors used in the story "Evening with a Horse" by the author Togay Murad.  There are three main types of metaphors, and the meaning is transferred based on the similarity of form, sign, and movement.  Based on this classification, the metaphors were analyzed in groups and examples were given from the story.